A Champlain Sea phocid seal fossil from the Champlain Lowland at Plattsburgh, New York - Franzi, David A.; Feranec, Robert; Rayburn, John A. (Geological Society of America (GSA), Boulder, CO, United States (USA), 2010)
A SUNY Plattsburgh environmental geotechnology class uncovered several bones, most likely from a harbor seal (Phoca vitulina), from exposures of Champlain Sea mud at the former Plattsburgh Air Force Base marina. The glacial section at the site contains a complete record of late Wisconsinan deglaciation in the Champlain lowland. A 1.5 to 2.0 meter thick section of fresh water ostracode (Candona subtriangulata) bearing, thinly laminated proglacial lacustrine rhythmites overlie massive gray diamicton near the base of the section. The lacustrine rhythmites contain a 0.0 to 0.2 meter thick layer of medium sand that may record one or more breakout floods from the Ontario and St. Lawrence lowlands. The lacustrine rhythmites grade upward to thinly laminated transitional rhythmites that contain marine and fresh water microfaunal assemblages. Approximately 1.5 to 2.0 meters of thinly laminated to massive, fossiliferous marine mud overlies the transitional facies, which in turn grades upward to an approximately 7-meter thick section of horizontally bedded silt and sand. The seal bones came from massive marine mud just below the transition to silt and sand. The accidental fossil find occurred as the class collected mud samples for a slope stability analysis of the bluffs along the present shoreline of Lake Champlain. The collection consists of the tibia and fibula from both legs, four vertebrae, four ribs, an astragalus, a tarsal bone, a phalange, a molar and half of the mandible with a canine tooth attached. Collagen extracted from a piece of fibula has been sent to the National Ocean Sciences Accelerator Mass Spectrometry Facility (NOSAMS) for radiocarbon dating. The find represents the second phocid fossil recovered from the Champlain lowland. The left tibial shaft from another harbor seal, originally misidentified as a hooded seal (Cystophora cristata), was found in Plattsburgh in 1901. Harbor seals on the east coast of North America presently range from the mid-Atlantic region to the Canadian Arctic.
id: 2214; Source type: conferencepapers&proceedings; Object type: Article; Object type: Conference Paper; Copyright: GeoRef, Copyright 2010, American Geological Institute. Reference includes data supplied by the Geological Society of America, Boulder, CO, United States; CSAUnique: 2010-092590; AccNum: 2010-092590; ISSN: 0016-7592; CODEN: GAAPBC
Keywords: 11; 24; bones; Carnivora; Cenozoic; Champlain Lowland; Champlain Sea; Chordata; Clinton County New York; Eutheria; lacustrine environment; Lake Champlain; lake sediments; Mammalia; New York; North America; Phoca; Phocidae; Pinnipedia; planar bedding structures; Plattsburgh New York; Pleistocene; Quaternary; Quaternary geology; rhythmite; sedimentary structures; sediments; taphonomy; Tetrapoda; Theria; United States; upper Pleistocene; upper Wisconsinan; Vertebrata; Vertebrate paleontology; Wisconsinan

Oxygen and carbon isotope records of calcareous nannofossils from the west Philippine Sea during the last 190ka - Jingtao, Zhao; Li, Tiegang; Chang, Fengming; Li, Jun (Earth Science.Journal of China University of Geoscience, 2008)
The piston core Ph05-5 recovered from the West Philippine Sea(16.049 degrees N, 124.344 degrees E, water depth 3382m) was used to study the delta (super 18) O and delta (super 13) C variations of calcareous nannofossils. The delta (super 18) O values of calcareous nannofossils were obviously lower in Holocene and the last interglaciation than those in the last and the penultimate glaciation. During the last 190 ka the nannofossil delta (super 18) O values were positively correlated with those of planktonic and benthic foraminifera from the same core. But the average delta (super 18) O value of nannofossils was 0.431X10 (super -3) , higher than that of planktonic foraminifera Globigerinoides rubber, and was 0.410X10 (super -3) , lower than that of planktonic foraminifera Neogloboquadrina dutertrei. All the above three average delta (super 18) O values were much lower than those of benthic foraminifera Cibicides wullerstorfi. The change of nannofossil delta (super 13) C values showed similar trends with the absolute abundance of calcareous nannofossils in core Ph05-5, which also indicates the primary productivity variations in the West Philippine Sea. The primary productivity stayed at a stable but relatively low level at MIS 6 and MIS 5e.There was an abrupt rise at the beginning of MIS 5d for the primary productivity which retained high value until 25 ka BP. The primary productivity showed a slight decline during MIS 2 and MIS 1, but still higher than that of MIS 6 and MIS 5e.
id: 1933; NO: Source type: scholarlyjournals; Object type: Article; Copyright: GeoRef in Process, Copyright 2011, American Geosciences Institute. After editing and indexing, this record will be added to Georef.; CSAUnique: 570969-5; AccNum: 570969-5; ISSN: 1000-2383; Peer Reviewed: true
Keywords: 02D; 24; algae; biochemistry; C-13/C-12; carbon; Cenozoic; Foraminifera; Geochemistry; Holocene; Invertebrata; Isotope geochemistry; isotope ratios; isotopes; Last glacial maximum; microfossils; nannofossils; north pacific; Northwest Pacific; O-18/O-16; oxygen; Pacific Ocean; paleo-oceanography; Philippine Sea; Plantae; Pleistocene; productivity; Protista; Quaternary; Quaternary geology; Stable isotopes; upper Pleistocene; West Pacific